Assessment of milk adulteration in the commercially available milk for the consumers in Cauvery delta region of Tamil Nadu, India - Dhanalakshmi, M; Balakrishnan, S; Sangeetha, A; Manimaran, K; Jayalalitha, V (Indian Journal of Dairy Science, 2020)
Milk is an old age symbol of trusted purity has not been the exception for the pull strings of millennium developments. In recent years, milk available in the markets is deviated from its inherent nutritional composition because of adulteration. This study was designed to assess the quality with regards to adulteration in milk which is supplied to the consumers  in and around the Cauvery delta regions of Tamil Nadu. A total of  75 milk samples were randomly collected from various sources like street vendors, tea shops, restaurants, hotels and commercially available pasteurized  milk outlets and tested for the presence of common adulterants like starch, sugar, glucose, detergents, neutralizers, salt and skim milk powder using a kit for adulteration testing of milk (Himedia). This study revealed that the presence of detergent (48%), sodium chloride (36%), skim milk powder (29.3%), neutralizer (18%), sugar (12%), starch (8%) and urea (8%).  It was found that tea shops happened to be a major source followed by restaurant and hotels. It is concluded that awareness needs to be created among the public about the health hazards of adulterants.